Towards the Universal Health Coverage in Ghana: An exploratory, cross-sectional study on the National Health Insurance Scheme - Richard Boateng; Alfred E Yawson (Journal of Health and Social Sciences)
Introduction: This study is aimed to analyze the progress towards the attainment of Universal Health Coverage (UHC) in Ghana after the establishment of the ‘National Health Insurance Scheme’ (NHIS), which is a universal health care system created in 2003 to guarantee the right of care for all. Method: A cross-sectional survey was conducted in 2017 on 300 adult participants, who were recruited by a convenience random sampling from subscribers of the formal and informal sectors, living in Accra, Ghana. A questionnaire ad hoc was administered to study subscribers’ perceived quality of healthcare services delivered by NHIS and their perception about UHC and two discrete indicators of healthcare system performance such as Universal Healthcare Access (UHA) and Financial Risk Protection (FRP). Data analysis was conducted through SPSS 21 and AMOS 21, employing basic analysis such as reliability, principal component and model fit analysis. Additionally, the structural model analysis was conducted to examine the relationship between antecedent and outcomes variables. Results: In our study, positive perception of NHIS services enjoyed during the last year was predictive of FRP (CR = 5.324, P < 0.001), UHA (CR = 3.736, P < 0.001) and UHC (CR = 4.159, P < 0.001) of NHIS. In addition, UHA and FRP were found to be good predictors in the relationship between perceived quality of healthcare services delivered by NHIS and UHC (CR = 5.823, P < 0.001 and CR = 2.097, P < 0.05, respectively). Discussion and Conclusion: Findings of our study showed that perceived quality of healthcare services delivered by NHIS may play a certain role on the attainment of UHC both directly and by mediating effects of UHA and FRP. Therefore, good healthcare services provided by NHIS can promote universal healthcare access and financial risk protection as major catalysts towards the attainment of UHC in Ghana.